Semangat Reformasi Persembahan Umat Pasca Pembuangan Menurut Maleakhi 3:6-12 - Rudolf Panggabean (Sekolah Tinggi Teologi Torsina Surakarta, 2021)
The tithe offering to God shows the repentance of the people to Him. Obedience in giving a true tithe offering is a practice of covenant between God and His people, but n its implementation, people break their covenants against God's decree. people still practice the wrong practices of worshipping God, especially regarding things. The real tithe is not of how much the people give to God, but rather a form of obedience to Him. This condition was conveyed by Malachi to the people of Israel. This study aims to analyze the text of Malachi 3:6-12 to gain an understanding of the spirit of reform of post-exile offerings. The method used in this study is qualitative by applying descriptive methods through the analysis of the social history of the text. In terms of the spirit of reform of the people after the exile according to the text of Malachi 4:6-12, it is obtained an understanding of the spirit of reform of the offering of the people as obedience through thanksgiving to God and to the common welfare.AbstrakPersembahan persepuluhan kepada Allah menunjukkan pertobatan umat kepada-Nya. Ketaatan dalam memberikan persembahan persepuluhan yang benar merupakan salah satu praktik perjanjian antara Allah dan umat-Nya, namun pada pelaksanaannya, umat melanggar perjanjian mereka terhadap ketetapan Allah itu. umat masih saja melakukan praktik peribadatan yang salah kepada Allah, khususnya mengenai persembahan perse-puluhan. Kondisi ini disampaikan Nabi Maleakhi kepada umat Israel. Penelitian ini bertujuan untuk menganalisa teks Maleakhi 3:6-12 untuk mendapatkan pemahaman semangat reformasi persembahan umat pasca pembuangan. Metode yang dipakai dalam penelitian ini adalah kualitatif, dengan menerapkan metode deskriptif melalui analisis sejarah sosial teks. Dalam hal semangat reformasi persmbahan umat pasca pembuangan menurut teks Maleakhi 4:6-12, maka didapatkan pemahaman mengenai semangat reformasi persembahan umat sebagai ketaatan melalui ucapan syukur kepada Allah dan untuk kesejahteraan bersama